Equity in healthcare for coronary heart disease, Wales (UK) 2004-2010: A population-based electronic cohort study. - William King; Arron Lacey; James White; Daniel Farewell; Frank Dunstan; David Fone (PLoS ONE)
Background Despite substantial falls in coronary heart disease (CHD) mortality in the United Kingdom (UK), marked socioeconomic inequalities in CHD risk factors and CHD mortality persist. We investigated whether inequity in CHD healthcare in Wales (UK) could contribute to the observed social gradient in CHD mortality. Methods and findings Linking data from primary and secondary care we constructed an electronic cohort of individuals (n = 1199342) with six year follow-up, 2004-2010. We identified indications for recommended CHD interventions, measured time to their delivery, and estimated risk of receiving the interventions for each of five ordered deprivation groups using a time-to-event approach with Cox regression frailty models. Interventions in primary and secondary prevention included risk-factor measurement, smoking management, statins and antihypertensive therapy, and in established CHD included medication and revascularization. For primary prevention, five of the 11 models favoured the more deprived and one favoured the less deprived. For medication in secondary prevention and established CHD, one of the 15 models favoured the more deprived and one the less deprived. In relation to revascularization, six of the 12 models favoured the less deprived and none favoured the more deprived-this evidence of inequity exemplified by a hazard ratio for revascularization in stable angina of 0.79 (95% confidence interval 0.68, 0.92). The main study limitation is the possibility of under-ascertainment or misclassification of clinical indications and treatment from variability in coding. Conclusions Primary care components of CHD healthcare were equitably delivered. Evidence of inequity was found for revascularization procedures, although this inequity is likely to have only a modest effect on social gradients in CHD mortality. Policymakers should focus on reducing inequalities in CHD risk factors, particularly smoking, as these, rather than inequity in healthcare, are likely to be key drivers of inequalities in CHD mortality.